2021
DOI: 10.3390/land10121351
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Family Capital on Farmers’ Participation in Farmland Transfer: Evidence from Rural China

Abstract: Family capital provides diverse and effective resources for production and livelihood of farmers, and thus profoundly determines farmers’ behavior in the decision-making process, yet the specific impact of family capital on farmers’ participation in farmland transfer has not been adequately examined. Based on a theoretical analysis, this paper divides family capital into four dimensions: human capital, economic capital, social capital, and cultural capital, and empirically analyzes the impact of different type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Heilongjiang, Shaanxi, Inner Mongolia, and Hubei account for more than 40% of China's grain production, whereas Qinghai, Gansu, Sichuan, Chongqing, Guizhou, and Guangxi produce more than 40% of the country's cash crops. From a national perspective, planting cash crops is likely in the west and southwest and grain crops in the northeast, northwest, and central regions, demonstrating the accuracy of the sample data; it is consistent with the divide between China's main grain-producing regions and non-major grain-producing regions 5 .…”
Section: Descriptive Statisticssupporting
confidence: 68%
See 1 more Smart Citation
“…Heilongjiang, Shaanxi, Inner Mongolia, and Hubei account for more than 40% of China's grain production, whereas Qinghai, Gansu, Sichuan, Chongqing, Guizhou, and Guangxi produce more than 40% of the country's cash crops. From a national perspective, planting cash crops is likely in the west and southwest and grain crops in the northeast, northwest, and central regions, demonstrating the accuracy of the sample data; it is consistent with the divide between China's main grain-producing regions and non-major grain-producing regions 5 .…”
Section: Descriptive Statisticssupporting
confidence: 68%
“…Accordingly, in order to ensure national grain security, the Chinese government has emphasized farmland redlining, grain self-sufficiency, and the absolute security of staple foods in every published "Central No.1 Document" since 2013. Developing land rental markets is a commonly suggested method for increasing grain yields and farm productivity in China [5]. The argument is that land fragmentation is a major obstacle to increasing farm productivity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, household characteristics [ 22 ], For example, the education level [ 23 ], physical condition and age of the household head influence the willingness to transfer farmland [ 24 ]. Ali’s studies showed that female-headed households are more inclined to rent out land due to the deficiencies of labour force in the household.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Households with non-agricultural employment choose to sell most of their grain immediately after harvest because these non-agricultural employees generally do not eat at home, and the families need less grain. Meanwhile, non-agricultural employees are generally young and middle-aged labourers and selling most of the maize immediately after harvest can reduce grain management and the marketing burden on other family members (Xu et al , 2021). Moreover, households with savings have a better life and might rely on the market to meet consumption needs (Leight, 2020).…”
Section: Estimation Results and Robustness Testmentioning
confidence: 99%